Fabrication and characterization of free-standing thick-film piezoelectric cantilevers for energy harvesting - Kok, Swee Leong; White, Neil; Harris, Nick (2009)
Research into energy harvesting from ambient vibration sources has attracted great interest over the last few years, largely as a result of advances in the areas of wireless technology and low-power electronics. One of the mechanisms for converting mechanical vibration to electrical energy is the use of piezoelectric materials, typically operating as a cantilever in a bending mode, which generate a voltage across the electrodes when they are stressed. Typically, the piezoelectric materials are deposited on a non-electro-active substrate and are physically clamped at one end to a rigid base. The presence of the substrate does not contribute directly to the electrical output, but merely serves as a mechanical supporting platform, which can pose difficulties for integration with other microelectronic devices. The aim of this paper is to describe a novel thick-film free-standing cantilever structure that does not use a supporting platform and has the advantage of minimizing the movement constraints on the piezoelectric material, thereby maximizing the electrical output power. Two configurations of the composite cantilever structure were investigated: unimorph and multimorph. A unimorph consists of a pair of silver/palladium (Ag/Pd) electrodes sandwiching a laminar layer of lead zirconate titanate (PZT). A mulitmorph is an extended version of the unimorph with two pairs of Ag/Pd electrodes and three laminar sections of PZT.